Analysis on energy consumption of blended-wing-body underwater glider. (30th April 2020) - Du, Xiaoxu; Zhang, Lianying
As a new type of underwater observation platform, underwater glider is widely used in marine explorations and military surveys, and most gliders are powered by their own batteries whose capacities are limited. It is therefore necessary to analyze the energy consumption of underwater glider. In this article, the variation law of seawater density changing with depth is considered; based on the theory of rigid body dynamics, the motion model of blended-wing-body underwater glider is established; the energy consumption model of each component module is accounted by analyzing the energy consumption composition in the working process of blended-wing-body underwater glider; and the energy consumption under different navigation depths, different glide ratios, and different buoyancy adjustments regulation is simulated. The results demonstrate that as the glide depth is increased, the total energy consumption increases in a single cycle and decreases per gliding distance, leading to a smaller energy consumption ratio for the attitude adjustment module; on the other hand, as the buoyancy adjustment is increased, more energy is consumed in a single cycle and less energy is consumed per gliding distanced, resulting in a larger energy consumption ratio for the attitude adjustment module. As the glide ratio increases, the total energy consumption in a single cycle first increases and then decreases, while the energy consumption of per gliding distance and the energy consumption ratio of the attitude adjustment module are decreased.